International conference “The Caucasus at the crossroads of international trade and cultural exchange (from ancient times to the present)” - Monika Mirzoyan (Banber Arevelagitut'yan Instituti)
The International Conference "The Caucasus at the Crossroads of Internation-al Trade and Cultural Exchange (from ancient times to the present)" was held at the National Academy of Sciences of RA on September 5-6, 2022. It was organized by the Institute of Oriental Studies of NAS RA and the Institute of History and Ethnology of Ivane Javakhishvili Tbilisi State University. The conference was attend-ed by about forty researchers from research centers and universities in Armenia, Georgia, Russia, Japan, the United States of America, Iran, and Poland. At the beginning of the conference welcoming speeches were delivered by Academician-Secretary of the Division of Armenian Studies and Social Sciences of NAS RA Academician Yuri Suvaryan, Director of the Institute of the Oriental Studies of NAS RA Robert Ghazaryan, and Director of the Institute of History and Ethnology of Ivane Javakhishvili Tbilisi State University Giorgi Tcheishvili. In his opening remarks, academician Yuri Suvaryan noted, "the Caucasus is an important cross-road where the interests of many nations and states have been intersecting. I hope this conference will be a key step for the continued development of Caucasian studies. Under current geopolitical conditions new challenges and difficulties are emerging, and this conference should also have a practical purpose, to work out a strategy which will help to face the modern scientific and also geopolitical chal-lenges coming up for the Caucasian peoples.